ANALISIS PENGELOLAAN ALOKASI DANA DESA (ADD) DALAM PEMBERDAYAAN MASYARAKAT DESA MARGOMULYO KECAMATAN JUWANA KABUPATEN PATI - Dari, Diah Wulan; Warsono, Hardi (Journal of Public Policy and Management Review, 2018)
Inequality of development between rural and urban areas encourage the central government to provide somes insentives to the village’s government, one of which is through the Alokasi Dana Desa (ADD). The income ADD must be managed well, which is it can be used for community empowerment in order to encourage the intensify of community’s welfare. The common problem that always happened in society is how to manage these fund in community empowerment.? The aim of this research is to know the process of how to manage this ADD and the influencing factors, and also how to improve the management of this funds in Margomulyo’s village. This study is descriptive-qualitative research by using Spredley’s data analysis method and source’s triangulation technique to do validity test. The result of this research shown that planning step of the ADD in community empowerment is in the awakening level of empowerment’s process that can be seen from unmaximal effort to realize the community about their potency. The Organizing phase is still in understanding level, it can be seen from how the miscommunication still happened around the stakeholder. Actuating phase in this research shown that the empowerment is in using level, it can be seen from people’s participation in monitoring process. The influencing factors that found in this research are leadership, human resources, management’s process, community’s participation and the culture.